2022
DOI: 10.1038/s41419-022-05310-w
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation-mediated degradation of hnRNPA2B1 contributes to hypertriglyceridemia pancreatitis

Abstract: Hypertriglyceridemia-induced acute pancreatitis (HTGP) is characterized by the acute and excessive release of FFA produced by pancreatic lipases. However, the underlying mechanisms of this disease remain poorly understood. In this study, we describe the involvement of the RNA binding protein hnRNPA2B1 in the development of HTGP. We used palmitic acid (PA) and AR42J cells to create a model of HTGP in vitro. RT-PCR and western blot analyses revealed a decrease in the level of hnRNPA2B1 protein but not mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…39 It is also reported that PA treatment led to a reduction in heterogeneous nuclear ribonucleoproteins (hnRNPs) and serine-rich splicing factor 3 (SRSF3) protein levels by neddylationmediated proteasomal degradation in AR42J and HepG2 cells, respectively. 40,41 Since MG132 significantly prevented FFA-induced IPMK reduction, we speculate that FFAmediated modification of IPMK may trigger its degradation via proteasomal systems.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…39 It is also reported that PA treatment led to a reduction in heterogeneous nuclear ribonucleoproteins (hnRNPs) and serine-rich splicing factor 3 (SRSF3) protein levels by neddylationmediated proteasomal degradation in AR42J and HepG2 cells, respectively. 40,41 Since MG132 significantly prevented FFA-induced IPMK reduction, we speculate that FFAmediated modification of IPMK may trigger its degradation via proteasomal systems.…”
Section: Discussionmentioning
confidence: 86%
“…Saturated fatty acid such as PA has been shown to upregulate the proteolytic system in skeletal muscle, 36–38 and facilitates ubiquitination of cellular proteins leading to their degradation via the ubiquitin−proteasome pathway in HepG2 cells 39 . It is also reported that PA treatment led to a reduction in heterogeneous nuclear ribonucleoproteins (hnRNPs) and serine‐rich splicing factor 3 (SRSF3) protein levels by neddylation‐mediated proteasomal degradation in AR42J and HepG2 cells, respectively 40,41 . Since MG132 significantly prevented FFA‐induced IPMK reduction, we speculate that FFA‐mediated modification of IPMK may trigger its degradation via proteasomal systems.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acid such as palmitic acid has been shown to upregulate the proteolytic system in skeletal muscle (Perry et al, 2018;Woodworth-Hobbs et al, 2014;Yang et al, 2013), and facilitates ubiquitination of cellular proteins leading to their degradation via the ubiquitinproteasome pathway in HepG2 cells (Ishii, Maeda, Tani, & Akagawa, 2015). It is also reported that PA treatment led to a reduction in heterogeneous nuclear ribonucleoproteins (hnRNPs) and serine-rich splicing factor 3 (SRSF3) protein levels by neddylation-mediated proteasomal degradation in AR42J and HepG2 cells, respectively (Chen, Wang, Xia, Zhang, & Zhao, 2022;Kumar et al, 2019). Since MG132 significantly prevented FFA-induced IPMK reduction, we speculate that FFA-mediated modification of IPMK may trigger its degradation via proteasomal systems.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, HnRNPA2B1 has an important regulatory role in preventing HTG damage to cells. Because neddylation is responsible for regulating the post-translational expression level of HnRNPA2B1, drugs targeting pharmacological inhibitors of neddylation may provide therapeutic benefit to patients with HTG-AP [66].…”
Section: Therapymentioning
confidence: 99%